2015
DOI: 10.1088/0004-637x/807/2/138
|View full text |Cite
|
Sign up to set email alerts
|

Chitah: STRONG-GRAVITATIONAL-LENS HUNTER IN IMAGING SURVEYS

Abstract: Strong gravitationally lensed quasars provide powerful means to study galaxy evolution and cosmology. Current and upcoming imaging surveys will contain thousands of new lensed quasars, augmenting the existing sample by at least two orders of magnitude. To find such lens systems, we built a robot, Chitah, that hunts for lensed quasars by modeling the configuration of the multiple quasar images. Specifically, given an image of an object that might be a lensed quasar, Chitah first disentangles the light from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 47 publications
0
59
0
Order By: Relevance
“…These other search methods are described in more detail in Agnello et al (2017). We provide here a brief summary: (1) the Gaussian Mixture Model (GMM) method of Ostrovski et al (2017),w h i c h uses supervised machine learning in a five-dimensional optical plus infrared color space and identified DES J0408-5354 as a candidate pair (D+G1 not found separately in J band due to blending noted above); (2) CHITAH (Chan et al 2015), which uses pixel-based automatic recognition on grizY cutout images and identified the system as a candidate pair (not flagged as a quad because the fourth image G2 is too red);and(3) the Artificial Neural Network method of Agnello et al (2015aAgnello et al ( , 2015b, which uses griz and W W 1 2 magnitudes and identified DES J0408-5354 as a candidate extended quasar. Figure 2 shows how the system was flagged by the GMM method as a candidate, due to the quasar-like colors of its components.…”
Section: Search and Discoverymentioning
confidence: 99%
“…These other search methods are described in more detail in Agnello et al (2017). We provide here a brief summary: (1) the Gaussian Mixture Model (GMM) method of Ostrovski et al (2017),w h i c h uses supervised machine learning in a five-dimensional optical plus infrared color space and identified DES J0408-5354 as a candidate pair (D+G1 not found separately in J band due to blending noted above); (2) CHITAH (Chan et al 2015), which uses pixel-based automatic recognition on grizY cutout images and identified the system as a candidate pair (not flagged as a quad because the fourth image G2 is too red);and(3) the Artificial Neural Network method of Agnello et al (2015aAgnello et al ( , 2015b, which uses griz and W W 1 2 magnitudes and identified DES J0408-5354 as a candidate extended quasar. Figure 2 shows how the system was flagged by the GMM method as a candidate, due to the quasar-like colors of its components.…”
Section: Search and Discoverymentioning
confidence: 99%
“…Fortunately, the DES image quality (median seeing ∼ 0.9 ) is better than that of SDSS, so one can rely on more accurate morphological information for candidate selection. New techniques have been developed in order to address this challenge (Agnello et al 2015;Chan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Image simulations of strong lensing systems have been used to predict that current and future wide-field galaxy surveys (e.g, DES, HSC survey, KiDS, LSST, Euclid, and WFIRST ) will produce several to hundreds of thousands of galaxy-galaxy strong lensing systems (Collett 2015). Many efforts have recently focused on employing techniques from computer vision and machine learning to go beyond traditional approaches such as visual searches of "blue" arcs near "red" galaxies (Diehl et al 2017), goodness of fit examinations after fitting a model to all candidates (Marshall et al 2009;Chan et al 2015), and public science challenges to discover new strong lensing systems in the large datasets. Neural networks have demonstrated to be able to distinguish between simulated lenses and non-lenses (Lanusse et al 2017;Hezaveh et al 2017).…”
Section: Strong Lensing Simulations and Machine Learning Methodsmentioning
confidence: 99%